Analysis of the use of fiber concrete in lintel beams as an alternative to traditional prefabricated solutions - Szymon Sawczyński; Anees Ahmed Vighio; Muhammad Yousaf Raza Taseer (Budownictwo o Zoptymalizowanym Potencjale Energetycznym, 2025)
Sustainable construction focuses on minimizing raw material consumption and optimizing construction processes in terms of both economy and ecology. Lintels are among the structural elements where material usage can be significantly reduced. Traditionally used prefabricated beams, while convenient, often exhibit excessive strength relative to actual loads, leading to unnecessary costs and an increased carbon footprint. This article examines the potential use of fiber-reinforced concrete – concrete strengthened with polymer and steel fibers – as an alternative to traditional lintels. Comparative strength tests were conducted on four beam variants, including those reinforced with fiber reinforcement. The results indicate that despite having a lower load-bearing capacity compared to prefabricated beams, fiber-reinforced concrete can be a viable option in certain scenarios, particularly where lintels do not serve a primary load-bearing function. Additionally, the article aligns with contemporary construction trends, such as the use of waste materials in concrete reinforcement, by considering the incorporation of plastic fibers as an alternative to traditional steel reinforcement. The use of recycled fibers – including plastics, reclaimed steel, and carbon fibers from the aerospace and automotive industries – can enhance the mechanical properties of concrete while reducing its environmental impact. These innovations align with the principles of the circular economy, providing both ecological and economic benefits. The research findings suggest that fiber-reinforced concrete lintels can contribute to reducing construction costs and limiting the consumption of natural resources, making them a compelling alternative to conventional solutions.